AEROBIC DEGRADATION KINETICS STUDY ON DOMESTIC SOLID WASTE COMPONENT (LABORATORY SCALE AND FIELD SCALE) - Meilany S, Lya
Abstract: Degradation kinetics number is highly affected by the solid waste composition and characteristic. Due to the fact that solid waste composition is very heterogen and variative, the degradation kinetics will vary also. Until now, composting application is widely used, both naturally and by using various kind of treatment in order to accelerate the process. One of the effort mostly being applied in the field is by mixing the solid waste with agriculture waste such as bran as a source of additional carbon, and the use of inocula. To support the effort this field application, in this research, has been doing the test of aerobic degradation acceleration on household and market solid waste, with some treatment, such as addition of bran and inocula. The research is done in laboratory scale for solid waste degradation test, and field scale for composting process application test. The result of laboratory test will be used as a basic of application on the field by considering a correction factor coefficient. The main parameter of that degradation is a solid waste volatile weight. The result of periodic observation and data process of volatile weight in a form of exponential equation are used as an approach to estimate degradatiion rate in that composting process. Another paramater that observed are water content, wet weight, carbon, nitrogen, C/N ratio. From laboratory scale degradation test, is obtained degradation rate value (k) for various kind of solid waste and treatment, as follows: • Household solid waste : 0,0254 day-1 • Household solid waste + INC (0,75%) : 0,0307 day-1 • Household solid waste + INC (0,75%) + bran (1/20) : 0,0328 day-1 • Market solid waste : 0,0226 day-1 • Market solid waste + INC (0,75%) : 0,0296 day-1 • Market solid waste + INC (0,75%) + bran (1/20) : 0,0333 day-1 . Adding inocula to degradation / composting process that function as a starter accelerate the process of 17.5 - 22.5%. While adding bran to the degradation / composting process will cause : accelerate the process 22,5 - 27.0% decreasing solid waste water content ± 7% increasing carbon content 41 - 55% increasing C/N ratio to be C/N optimum for composting (±30).